MANAJEMEN KINERJA, KINERJA ORGANISASI SERTA IMPLIKASINYA TERHADAP KUALITAS PELAYANAN ORGANISASI SEKTOR PUBLIK - Teni Listiani (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2011)
Up to now people still regard the quality of public service has yet to be improved. Timeliness, bribery, discrimination,mhigh cost, and red tapes are among weaknesses observed in government organizations providing public service delivery. Many studies suggest the poor quality public service is due to the inadequate organization performance. This inadequate organization performance is thought to be caused by the unability on the part of organizations to manage their performance based upon the aspects of personal, leadership, teamwork, system, and condition.